2006
DOI: 10.3109/s10165-006-0520-4
|View full text |Cite
|
Sign up to set email alerts
|

Anticyclic citrullinated peptide antibodies in juvenile idiopathic arthritis

Abstract: Anticyclic citrullinated peptide (anti-CCP) antibodies have been detected in patients with juvenile idiopathic arthritis (JRA), particularly in those with polyarticular JIA. We analyzed the presence of anti-CCP antibodies of the IgG class in sera of patients with defined juvenile idiopathic arthritis (JIA) of various subgroups. One hundred and fifty-nine serum samples were investigated. Forty-five patients were diagnosed with JIA (15 male and 30 female) aged 1.9-17.3 years (median 12.9, mean 11.0). Thirty-eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 4 publications
0
10
0
2
Order By: Relevance
“…Numerous studies have shown that IgM RF-positive polyarthritis patients have a higher prevalence of anti-CCP antibodies [36][37][38][39][40][41][42][43][44]45 We have also shown that the measurement of IgA, IgM, and IgG anti-CCP antibody isotypes early in the course of JIA may be beneficial to distinguish aggressive disease and possibly initiate more aggressive treatment earlier in those patients [48•]. These patients have been shown to have higher immune complex levels by the anti-Fc III method of detection and are noted to have increased disease activity [49•].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that IgM RF-positive polyarthritis patients have a higher prevalence of anti-CCP antibodies [36][37][38][39][40][41][42][43][44]45 We have also shown that the measurement of IgA, IgM, and IgG anti-CCP antibody isotypes early in the course of JIA may be beneficial to distinguish aggressive disease and possibly initiate more aggressive treatment earlier in those patients [48•]. These patients have been shown to have higher immune complex levels by the anti-Fc III method of detection and are noted to have increased disease activity [49•].…”
Section: Discussionmentioning
confidence: 99%
“…Brunner and Sitzmann [43] studied 45 JIA patients and noted elevated anti-CCP antibodies to secondgeneration peptides in only two patients. Both patients had IgM RF-positive polyarthritis.…”
Section: Anticyclic Citrullinated Peptide Antibodiesmentioning
confidence: 98%
“…Meanwhile, each ACPA had a different prevalence among the JIA subtypes, mainly because of the antigens used. Anti-CCP has been extensively studied in JIA, and the sensitivity of anti-CCP has been reported to be between 1.8 and 27.9% (Machado et al, 2005;Brunner and Sitzmann, 2006;Gilliam et al, 2008;Habib et al, 2008;Kuna et al, 2009). In the present study, anti-CCP was identified in 7 (8.9%) of 81 JIA patients, agreeing with the reported rates in most published studies, and the positivity (9.9%) was slightly improved by when anti-CCP3.1 IgG and IgA were used simultaneously to detect CCP.…”
Section: Discussionmentioning
confidence: 99%
“…But in the study by Brunner and Sitzmann [8] it was shown that these antibodies are only detected in patients with positive RF. This means that the pattern of JIA in patients with positive anti-CCP Abs resembles the RA.…”
mentioning
confidence: 94%